Comparing the “Typical Score” Across Independent Groups Based on Different Criteria for Trimming - Syed Yahaya, S.S.; Othman, Prof.Madya Abdul Rahman; Keselman, H. J. (2006)
Nonnormality and variance heterogeneity affect the validity of the traditional tests for treatment group equality (e.g. ANOVA F-test and t-test), particularly when group sizes are unequal. Adopting trimmed means instead of the usual least squares estimator has been shown to be mostly affective in combating the deleterious effects of nonnormality.